Stock Market Activities and Economic Growth in Nigeria: A Cointegration Approach - O., Ashamu Sikiru; A., Soyebo Yusuf (American Economic & Social Review, 2020)
Stock markets have been the main catalyst of economic growth in most economies. However, there are mix results on the exact nature of the influence of key stock market variables on economic growth in developing economies. Thus, this study examined the effect of stock market measures on economic growth in Nigeria. This paper employed an ex-post facto research design using annualized data obtained from the Central Bank of Nigeria (CBN) Statistical Bulletin and Stock Exchange Fact books for the period 1985 to 2017 and they were analysed using the error correction estimate regression technique at 5% level of significance. The result ecm (-1) is statistically sign and significant, stock market activities such as market capitalization (  = 0.0386, p > 0.05), number of deals (  = 0.0487, p < 0.05) and All share Index ( = 0.0921, p < 0.05) have positive influence on economic growth, while volume of trading (  = -0.6110, p < 0.05) has a negative effect on economic growth. These results suggested that all the specified variables except market capitalization have significant effect on economic growth in Nigeria. The study concluded that stock market activities influence the economic growth in Nigeria. Therefore, it is recommended that investors should take the advantage of the numerous opportunities offered by the stock market while market makers and regulators should continue to operate according to best market practices in order to ensure confidence and continuous patronage by various economic agents.